«Green» Technologies In The Construction Of Social Facilities. (2016) - Izvekova, Oksana; Roy, Vera; Murgul, Vera
Abstract: The article analyses the pattern of introduction of "green" technologies in the design and social sphere objects building. It is considered the issues of ecological-economic justification and effectiveness of "green" innovations in the social construction segment. Comparative analysis of international systems of environmental certification, namely: BREEAM and LEED. Examples of international and domestic experience in the construction of "green" objects on the example of schools in the United States and Russia are described. The article substantiates the advantages of "green" schools on the basis of the studies Gregory Katz.